Nivolumab to pembrolizumab switch induced a durable melanoma response: A case report. Issue 2 (January 2019) - Lepir, Tanja; Zaghouani, Mehdi; Roche, Stéphane P.; Li, Ying-Ying; Suarez, Miguel; Irias, Maria Jose; Savaraj, Niramol
Abstract: Rationale: While checkpoint inhibitors have revolutionized the treatment of melanoma, it is not known whether switching from one monoclonal antibody drug to another one would be justified in the case of a treatment failure. Herein, we report a case illustrating a durable response to pembrolizumab after a failure with nivolumab. Patient concerns: A 76-year-old white male noticed an enlarging papular lesion on his neck. Diagnosis: Malignant melanoma. Interventions: The patient underwent surgery in December 2013 and was found to have a B-Rapidly Accelerated Fibrosarcoma (BRAF) V600E mutated melanoma. Treatment with BRAF and MAPK/Erk kinase (MEK) inhibitors along with radiation was initiated. After 1 year, the disease progressed, and the treatment was switched to the cytotoxic T-lymphocyte antigen 4 (CTLA-4) blocking antibody, ipilimumab. As the tumor did not respond, the treatment was changed to programmed cell death receptor-1 (PD-1) blockers: nivolumab followed by pembrolizumab. Since the initial diagnosis, the tumor response was monitored by computed tomography (CT) scans. Immunohistochemistry (IHC) was also used for the assessment of programmed death ligand 1 PD-L1) expression in the neck, lung, and spleen lesions. Outcomes: The patient had an initial mixed response to nivolumab, but the disease ultimately progressed as evidenced by new metastases to the spleen, thus the treatment was switched to pembrolizumab. After 46 cycles of treatment, all sites of metastases disappeared, including a substantial shrinkage of the splenic metastasis. To gain understanding about the pharmacological differences between nivolumab and pembrolizumab, the PD-1–ligands interactions and conformational dynamics responsible for the PD-1/PD-L1 checkpoint blockade were investigated. The higher affinity of pembrolizumab might likely arise from a unique and large patch of interactions engaging the C'D loop of PD-1, thus forcing an important motion across the PD-1 immunoreceptor. Lessons: In this case report, we described the tolerance and response of a melanoma patient to a sequence of various agents, including ipilimumab, nivolumab, and pembrolizumab. To the best of our knowledge, this is the first clinical report highlighting differences between PD-1 blockers, as shown by the unexpected and durable response of the tumor to pembrolizumab, after a treatment failure with nivolumab. Abstract : Supplemental Digital Content is available in the text